Formulasi dan Uji Efektivitas Shampo Antiketombe Minyak Atsiri Seledri (Apium graveolens) terhadap Jamur Candida albicans: Formulation and Effectiveness Test of Anti-dandruff Shampoo Essential Oil of Celery (Apium graveolens) against Candida albicans Fungus - Asti Vebriyanti Asjur Asjur; Syaifullah Saputro; Tamzil Azizi Musdar; Mifta Khaerati Ikhsan (Jurnal Sains dan Kesehatan, 2022)
Celery plants contain limonene which belongs to the terpen group which has the potential as antifungal. This study aims to determinethe formulation of celer essential oil anti-dandruff gel shampoo that meets the physical quality requirements with a concentration 0f 1%, 5%, 10%, and to test the effectiveness of celery essential oil anti- dandruff gel shampoo against the fungus Candida albicans that causes dandruff. The research method was carried out experimentally by making an anti-dandruff gel shampoo formula containing celery (Apium graveolens) essential oil and testing its effectiveness against the fungus Candida albicans that causes dandruff using the well method. This study tested the antifungal effectiveness of essential oil anti-dandruff gel shampoo from formula 0 without celery essential oil (blank) as a negative control, formula 1 with 1% celery essential oil concentration, formula 2 with 5% celery essential oil concentration, formula 3 with 10% celery essential oil concentration, and dandruff shampoo containing 2% ketoconazole as a positive control. The result showed that 1. Celery essential oil can be formulated into anti-dandruff gel shampoo preparations that meet the physical quality requirement. 2. The antifungal effect of celery essential oil anti-dandruff gel shampoo on Candida albicans fungus is very strong with an average inhibitor zone diameter of 20,36 mm in formula 1 21,40 mm in formula 2, 21,60 mm in formula 3. There were differences in the inhibitor vale of each concentration of celery essential oil gel shampoo (p<0,05). Concentration of 5% has provided an optimal effect in inhibiting the growth of the fungus Candida albicans.